Effect of Dietary Organic Acids and Humic Substance Supplementation on Performance, Immune Response and Gut Morphology of Broiler Chickens - Aristimunha, P. C.; Mallheiros, R. D.; Ferket, P. R.; Cardinal, K. M.; Moreira Filho, A. L. B.; Santos, E. T. [UNESP]; Cavalcante, D. T.; Ribeiro, A. M. L. (Elsevier B.V., 2020)
This study evaluated the additive effects of a commercial feed supplementation blend (Ava Cid P)-consisting of humic substances, coated sodium butyrate, and a small acidifier portion-on the growth, immune response, and gut health of broiler chickens. A total of 540 female and 540 male broilers were raised from 1-49 d. On the first day, the animals were distributed in a completely randomized 2 x 5 factorial design (2 sexes and 5 treatments) with 7 replications of 15 birds each. The 5 treatments were 1) birds did not receive Ava Cid P (control); 2) birds received 0.91 kg/t of Ava Cid P from 1-21 d (AVA1-21); 3) birds received 0.91 kg/t of Ava Cid P from 1-21 d and 0.45 kg/t from 22-35 d (AVA1-35); 4) birds received 0.91 kg/t of Ava Cid P from 1-21 d and 0.45 kg/t from 22-42 d (AVA1-42); and 5) birds received 0.91 kg/t of Ava Cid P from 1-21 d, 0.45 kg/t from 22-35 d, and 0.23 kg/t from 36-49 d (AVA1-49). ANOVA and Tukey's tests were applied to compare the means (P < 0.05) between treatments. The Ava Cid P showed no effect on male or female growth performance or goblet cell density. However, the supplement modified gut morphometry, and jejunum villi were 32% higher at 9 and 35 d in the AVA1-35 birds compared with those of the control group. The apparent villus surface and villus height increased by 87% and 46%, respectively, in the AVA1-49 birds compared with the AVA1-21 birds. The expression of mucin 2 (MUC2) and tumor necrosis factor-alpha (TNF-alpha) were 1.6% and 0.9% lower in the AVA1-21 birds than in the control birds, but no effects were observed for interleukin-1 beta and interleukin-10. The Ava Cid P altered the mRNA expression of MUC2 and TNF-alpha and some characteristics of intestinal morphometry, but did not change the performance of broilers.
Keywords: animal performance; sodium butyrate; gut morphometry; humic acid